The salinity dependence of electrical conductivity and Archie's cementation exponent in shale formations - Zhong, Zhiqi; Rezaee, Reza; Josh, M.; Esteban, L.; Sarmadivaleh, Mohammad (ELSEVIER, 2022)
Electrical conductivity/resistivity is one of the key petrophysical parameters for well-log interpretation. However, in the shale formations, the fluid saturation determined from the well-known Archie-related equations is inaccurate. The commonly accepted reason is that clays within shale formations provide Cation Exchange Capacity (CEC) and additional surficial conduction pathways that are not properly accounted for in water saturation equations leading to the so-called “non-Archie” phenomenon. To investigate this, the Archie parameters were determined for 5 shale samples with CEC controlled by fully saturating different levels of pore water salinity. The electrical conductivity measurement underwent 2800 psi confining pressure to simulate reservoir conditions. The effective porosity was determined by comparing the sample weight in both dry and fully saturated states. Nuclear Magnetic Resonance (NMR) was used for the pore size distribution investigation. Only a small change in Archie's cementation exponent m was observed for different porewater salinities (0.1–0.15) indicating a minor contribution from CEC for shale samples, however, the change in pore water conductivity leads to altered electrical conduction pathways consistent with a volume averaging approach. In contradiction with commonly held belief, it is shown that the rock bulk conductivity and likewise Archie's cementation exponent, m, is not monotonically increasing with the pore water conductivity and therefore CEC has a minor effect on Archie's cementation exponent. This implies that confining pressure and therefore depth, is the main cause of the non-Archie phenomenon.